Analisis Kemandirian dan Kemampuan Keuangan Daerah serta Pengaruhnya Terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Sumatera Selatan - Royda; Riana, Dwi (Akuntansi dan Manajemen, 2019)
Fiscal decentralization aims to improve regional finance independency and reduce the fiscal dependency of central goverment. However, in practice, there are still many areas that rely on the assistance central finance for their regional development. The purpose of this study was to determine the level of development of local independence and financial ability as well as effects on economic growth in regency and city in the Sumatera selatan Province year 2008-2018.this research takes place in regency and city in the sumatera selatan province. While the data used in this research is financial data and economic growth 2008-2018 in the sumatera selatan province. Methods of data analysis in this study there are two kinds, the first is the ratio of local independence and the ratio of local financial ability. Secondly, to investigate the influence of independent variables on the dependent variable used multiple linear regression analysis tool. According to analysis result have been obtained as follows. The ratio of local financial independence of regions indicated by the ratio of the average rate so low, still be between 0%-25%. According the ratio of local financial ability of regions averages between 0%-10% which is low. Local self-reliance has positive and significant on economic growth. Regional financial capability have positive but not significant effect on economic growth in regency and city in the sumatera selatan province.